Commercialization of biotechnology product delivering the promise of technology - Arre, Grace Antoniette B. (University of the Philippines Diliman, 2004)
Biotechnology has been classified as a revolutionary technology and with its rapid development; it was foreseen to produce great impact to the society similar if not greater than the information and communication revolution of the twentieth century. Biotechnology is a set of powerful tools that employ living organisms or part of organisms to make or modify products, improve plants or animals or develop microorganisms for commercial use. All over the world, scientists are in constant pursuit of novel technologies that will alleviate pollution problems, improve the environment and the quality of life. Microorganisms, microbial enzymes and it's by products are being explored through biotechnology as alternative processes (Juma, 2000). Currently, the Philippines is confronted with waste management and pollution control as one of its major problems. The per capita solid waste generation in Metro Manila was estimated at 0.66 Kg as early as 1995. This amounted to approximately 6,102 tons of solid waste generated by the Metropolis on a daily basis. The Ecological Solid Waste Management Act of 2000 (RA 9003) enacted into law last January 26, 2001 by President Gloria Macapagal Arroyo was aimed to provide a system of analyzing solid waste concerns and to come up with solutions that would not pose any harm to the environment. Technologies that are environmentally sound such as composting, waste segregation, source reduction and recycling were included. In addition, Asian Development Bank, a multilateral development finance institution dedicated to reducing poverty in Asia and the Pacific, provided a US 1.25 million dollars technical assistance grant to help Metro Manila tackle its issue in waste management. The challenge however, lies in our ability to move up the technology ladder and find alternative technologies for waste management. This paper explored the technical and market feasibility for the commercialization of a product that evolved from a basic research. The project is envisioned to produce a locally manufactured microbial product for solid waste and wastewater treatment. Collaborative research with global companies manufacturing microbial products and enzymes for waste treatment is also being targeted. This paper recommends the development of a globally competitive microbial product for waste treatment through an effective technology transfer. In addition, this paper emphasized the importance of using technology commercialization frameworks as a tool in moving basic research form the laboratory to the marketplace. The use of such frameworks identifies and measures technical, business and financial aspects needed to successfully commercialize a product. It provides an organized approach to streamline the labyrinth of activities and avoid costly mistakes involved in the commercialization of a product.